SHADOW READING DALAM PEMBELAJARAN DARING PRIVAT: UPAYA MEMPERBAIKI KESALAHAN BACAAN HARAKAT BAHASA ARAB IBU-IBU - Medina, Fairuz Aida; Adzani, Syaffanah (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This classroom action research aims to describe efforts to improve harakat-reading errors among beginner adult learners through the application of the shadow reading technique in private online instruction. The study employed the CAR design of Kemmis McTaggart and was conducted over two cycles involving three beginner-level mothers who participated in learning activities via WhatsApp video calls; each session lasted approximately 60 minutes. Data were collected through qualitative observation sheets, field notes, and documentation of reading materials, while data analysis followed the qualitative approach of Miles and Huberman (data reduction, data display, and conclusion drawing). The results indicate that in Cycle I the participants still made several errors, particularly in mad (vowel length) and tasydid, but after the intervention in Cycle II the errors decreased significantly to an average of only 1–2 errors per participant. These findings illustrate that shadow reading can be used as an effort to improve harakat accuracy in private online learning with minimal facilities and adult participants, and they address a research gap regarding the application of shadowing among beginner mothers. The implications of this study include recommendations for incorporating repeated imitation exercises as an integral part of teaching harakat-based reading skills.